Design and Develop Mineral Water Bottle Vending Machine Prototype Using Programmable Logic Controller with Single Rotary Dropping Mechanism - Adenan, Intan Nur Shahzanani; Shaari, Muhammad Farid (Progress in Engineering Application and Technology, 2023)
Vending machines are a convenience that allows the sales and purchasing of goods from an automated machine. Machines are a cost-effective way to distribute goods and have the flexibility to be placed indoors or outdoors. They can operate continuously. They offer a range of goods to sell, and many accept credit cards. This project is to design and develop a mineral water bottle vending machine prototype using a programmable logic controller (PLC).